Progesterone decline threshold in predicting early pregnancy loss: a retrospective study - Wei, Yanling; Xin, Xiaoyu; Mu, Fangxiang; Wang, Fang (Frontiers in Endocrinology, 2025)
ObjectiveThe single measurement of serum progesterone is considered a predictor for non-viable pregnancies. However, the dynamic change in progesterone during early pregnancy loss (EPL) remains uninvestigated. This study evaluated the association between serum progesterone decline thresholds (PDT) and EPL.MethodsThis retrospective study included 664 pregnant women who visited a single medical center from January 2023 to December 2024. Based on pregnancy outcomes within the first trimester, participants were classified into the ongoing pregnancy group (n=388) and the EPL group (n=286). PDT was defined as a decline of ≥ 1/5 standard deviation (SD), 1/3 SD, 1/2 SD, 7/10 SD, or 1 SD compared with the last measurement of serum progesterone levels. SD was calculated based on the baseline serum progesterone levels. Multivariate logistic regression was applied to explore the association between PDT and EPL. Receiver operating characteristic (ROC) curve analysis was conducted to assess the diagnostic value of PDT. Subgroup analyses were performed to evaluate the robustness of the results.ResultsCompared with the ongoing pregnancy group, the EPL group had significantly lower baseline serum progesterone levels (P < 0.05). PDT ≥ 1/5 SD, 1/3 SD, and 1/2 SD were all significantly associated with EPL (OR [95%CI]=2.74 [1.76, 4.27], P < 0.001; OR [95%CI]=1.74 [1.18, 2.56], P=0.005; and OR [95%CI]=1.63 [1.07, 2.49], P=0.024, respectively). The corresponding AUC values were 0.502, 0.512, and 0.503. Additionally, a linear positive correlation was observed between the number of occurrences of PDT ≥ 1/3 SD and EPL. For each additional occurrence of PDT ≥ 1/3 SD, the risk of EPL increased by 36% (OR [95%CI]=1.36 [1.09, 1.70], P=0.006). Subgroup analyses supported the robustness of these results.ConclusionPDT ≥ 1/5 SD, 1/3 SD, and 1/2 SD are significantly associated with an increased risk of EPL. This suggests that these thresholds hold potential predictive value in EPL diagnosis and may help identify pregnant women at higher risk for early intervention.